The Use of Scrabble Games to Improve Students' Ability in Vocabulary - Nurul Rohmawati; Lailatul Masruroh (ELITE JOURNAL, 2023)
This study will examine how seventh-graders at MTs Assa'adah and Bungah respond to learning English vocabulary by playing scrabble games in order to increase their vocabulary mastery. Using classroom action research, the researcher selects class VII, which has 34 kids, as the subject for this study. The research employs an observation sheet to document the use of the scrabble game during the teaching and learning process and uses a questionnaire as an instrument to identify the issue. The researcher also administers tests to see whether pupils' vocabulary mastery has improved. The MTs, Assa'adah and I, were using scrabble games to teach English vocabulary, and the researcher discovered the following results: First, the process of teaching English vocabulary through scrabble games was going smoothly. The pupils appeared engaged in class, but some appeared to be giving less response than others. The second instance was when the teacher instructed the class to play some scrabble. The third was that the pupils were content with their education. Therefore, it can be said that the inclusion of the scrabble game has a positive impact on pupils' vocabulary Keywords: Vocabulary, Games, Scrabble